Antioxidant administration on the incidence of preterm premature rupture of membranes: a literature review - Winata, I Gde Sastra; Mahendrata, Prayascita; Wiraputri, Anak Agung Ratih Kusumadewi; Anwar, Meirisa Afifah Nurmalia; Jessica Nathalia (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2025)
One of the obstetric issues that can lead to consequences for both the mother and the unborn child is premature rupture of membranes (PROM). In Indonesia, 35% of pregnancies ended in preterm rupture of the membranes in 2013. The incidence of preterm pregnancy is 2% of all pregnancies, while the incidence of term pregnancy ranges from 6 to 19%. At 37 weeks gestation, the phrase